Introduction: Social Outbreak and Political Representation in Latin America - Navarrete-Yanez, B (Springer Nature Brazil, 2021)
Political representation in Latin America shows high levels of heterogeneity. In some countries we can see the weakening of the relationship between traditional political parties and social movements (Chile, Brazil, Colombia, Peru); meanwhile, in others the relationship is more stable (Uruguay and Argentina) and is even strengthened by the construction of parties built based on social movements (Bolivia and Ecuador). In this chapter we analyze the relationship between political parties and social movements in Latin America to identify the ruptures and continuities of Chile compared with the rest of the countries of the region. In the same way, it will set a general framework for analyzing the social outbreak and representation in Chile. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Chile; Latin America; Political parties; Political representation; Social movements; Social outbreak